Documents regarding the Ames Audubon Christmas bird count, 1977 - Ames Audubon Society (1977)
A group of documents related to the 1977 Ames Audubon Christmas Bird Count, including general instructions to the group leader (Wilmer and Lotus Miller) and a completed form of group participants with the party hours by habitat, miles, and time listed. Also included is checklist of birds seen during the last seven Ames Christmas Bird Counts annotated with the birds observed during the 1977 count. Epson - sheet feed/flatbed